2021
DOI: 10.14639/0392-100x-n1436
|View full text |Cite
|
Sign up to set email alerts
|

COVID-19 in the tonsillectomised population

Abstract: Objective. Interactions between SARS-CoV-2 and pharyngeal associated lymphoid tissue are thought to influence the manifestations of COVID-19. We aimed to determine whether a previous history of tonsillectomy, as a surrogate indicator of a dysfunctional pharyngeal associated lymphoid tissue, could predict the presentation and course of COVID-19. Methods. Multicentric cross-sectional observational study involving seven hospitals in Northern and Central Italy. Data on the clinical course and signs and symptoms of… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
6
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 10 publications
(6 citation statements)
references
References 21 publications
0
6
0
Order By: Relevance
“…A study from Italy reported that tonsillectomized adults had significantly higher risk of symptomatic COVID‐19, though an increase in hospitalization was not seen. 13 In addition, though studies have shown decreased immune function in chronic tonsillitis, it is unclear if adenotonsillar hypertrophy leads to an effective change in immune function in these organs. 14 Further studies are needed to understand the differences in local immune function in those children with tonsillar disease states including adenotonsillar hypertrophy, OSA, and chronic tonsillitis in addition to whether humoral immunity at these mucosal sites is protective against future infection.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…A study from Italy reported that tonsillectomized adults had significantly higher risk of symptomatic COVID‐19, though an increase in hospitalization was not seen. 13 In addition, though studies have shown decreased immune function in chronic tonsillitis, it is unclear if adenotonsillar hypertrophy leads to an effective change in immune function in these organs. 14 Further studies are needed to understand the differences in local immune function in those children with tonsillar disease states including adenotonsillar hypertrophy, OSA, and chronic tonsillitis in addition to whether humoral immunity at these mucosal sites is protective against future infection.…”
Section: Discussionmentioning
confidence: 99%
“…Whether local immunity in the tonsils protects from repeated SARS‐CoV‐2 infection is unknown. A study from Italy reported that tonsillectomized adults had significantly higher risk of symptomatic COVID‐19, though an increase in hospitalization was not seen 13 . In addition, though studies have shown decreased immune function in chronic tonsillitis, it is unclear if adenotonsillar hypertrophy leads to an effective change in immune function in these organs 14 .…”
Section: Discussionmentioning
confidence: 99%
“…Tonsillectomy does not seem to have a negative effect on the immune system, when humoral and cellular immunity is measured after surgery ( 84 86 ). During the COVID-19 pandemic, it was speculated that patients who underwent a tonsillectomy might have a higher risk for a more severe course of the SARS-CoV2 infections ( 87 , 88 ). This has remained so far unproven ( 89 ).…”
Section: Discussionmentioning
confidence: 99%
“…Different papers have been published so far regarding the importance of symptoms in early detection of COVID-19, especially alterations of sense of smell [ 17 20 ]. Since among laryngectomized patients, the nasal airflow is practically absent, other symptoms should be investigated (e.g., fever, dyspnea, fatigue…).…”
Section: Discussionmentioning
confidence: 99%